THE SPREAD OF PATHOLOGICAL PROCESSES IN UKRAINIAN FORESTS FOR THE PERIOD 1991-2009 - Ustskiy, I. M.; Musienko, S. I.; Nykytyuk, P. A. (Forestry and Forest Melioration, 2018)
Introduction The results of the state registration of forests of Ukraine as of 2011 indicate that in the total forest area of Ukraine for the last 15 years there is a 2.2-fold increase of the area not covered with forest vegetation, and is a 1,7-fold increase of logging area in the composition. There is gradual increase in the area of softwood trees by 1.7 times, and birch by 1.2 times. Alternatively, the area of spruce forests has decreased by 1.2 times. Successful implementation of the current tasks of forestry is impossible without knowledge of the consequences of the complex multifaceted impacts on forest ecosystems. Information on this set of issues is the basis for the forest condition changes forecast and is an outcome indicator of forest management. Materials and Methods The research was conducted by analyzing the materials on forests in which pathological processes (diseases, damage by natural factors, insect pests, fires, etc.) were observed as of 1994, 1997, 2000, 2003, 2006 and 2009 using software developed for this purpose. The spread of the pathological processes was estimated by the share of planted area, in which pathological processes were observed, in the wooded area. On our rating scale, the extent of pathological processes was estimated by the degree of their development: from 0.1 to 2.4 % - a slight degree, 2.5-5.0 % - average degree; 5.1-10.0 % - strong degree; 11.0 - 15.0 % - very strong degree; 15.1-20.0 % - critical degree; > 20,0 % - environmental disaster of district, regional or provincial significance. Results and Conclusion Collection and compilation of data on Ukrainian forests, in which there were marked pathological processes as of 1994, 1997, 2000, 2003, 2006 and 2009 years, showed that for the period of observations the area of such forests increased by 1.8 times. In 1997, the proportion of such plants was 2.4 % of forested area, and it was 5.6 % as of 2009. As of 2009, the most widespread were the pathological processes in spruce stands (19.6 % of spruce forested area), slightly less they were in oak (6.1 % of oak covered area) and pine (4.9 % of pine covered area) stands. For the observation period, the oak plantations, in which pathological processes were observed, grew unevenly by 12.5 thousand hectares, the pine ones - 8.5 thousand hectares, spruce - after 2000 - 24 thousand hectares every three years. As of 2020, in the case of the modern trends will continue, the area of pine stands undergoing the pathological processes in Ukraine will be about 140 thousand hectares , oak - 230 thousand hectares, spruce - about 500 thousand hectares, birch - 12 thousand hectares and alder - about 10 thousand hectares.